Pengaruh Profit Margin Rumah Sakit Dengan Kejadian Hais (Hospital Acquired Infections) (Studi Di 3 Rumah Sakit Tipe B) - Restuningdiah Dwi Sundari; Firman Pribadi (Jurnal Admmirasi, 2018)
Background: Hospital profit margins demonstrated the ability to generate profits or earnings. Low hospital profit margins can reduce the ability of the hospital to investment for increasingpatient safety programs, so it can have an impact on the increasing incidence of HAIs (Hospital Acquired Infections). The purpose of this study to determine the effect of the hospital profit margin onthe incidence of HAIs (Hospital Acquired Infections)that are consist of phlebitis, UTI (Urinary Tract Infection), SSI (Surgical Site Infection) and VAP (Ventilator Acquired Pneumonia). Methods: This study is a quantitative research with secondary data in cross sectional study. The financial data and HAIs (Hospital Acquired Infections) taken from 2012 to 2016. This study was perform in 3 type B hospitals. Analysis of data using linear regressions. Results and Discussion: The highest frequency of profit margins is ≥ 10%. The results of data analysis with CI (Confidence Interval) of 90% the effect of profit margin to phlebitis (p=0,004, x=-0,003), profit margin with UTI (Urinary Tract Infections) (p=0,002, x=-9,26), profit margin with SSI (Surgical Site Infection) (p=0,006, x=-0,002), profit margin with VAP (Ventilator Acquired Pneumonia) (p=0,009, x=-0,001). Conclusions and Recommendations: In Confidence Interval 90%, profit margins had effect on the incidence of HAIs (Hospital Acquired Infections)at the type B hospitals. There is a negative relationship between profit margins and the HAIs (Hospital Acquired Infections)incidence, which means that every increasing of 1 rupiah will reduce the incidence of HAIs (Hospital Acquired Infections) as a percentage.